The Bulk Heterojunction in Organic Photovoltaic, Photodetector, and Photocatalytic Applications. Issue 38 (5th August 2020) - Wadsworth, Andrew; Hamid, Zeinab; Kosco, Jan; Gasparini, Nicola; McCulloch, Iain
Abstract: Organic semiconductors require an energetic offset in order to photogenerate free charge carriers efficiently, owing to their inability to effectively screen charges. This is vitally important in order to achieve high power conversion efficiencies in organic solar cells. Early heterojunction‐based solar cells were limited to relatively modest efficiencies (<4%) owing to limitations such as poor exciton dissociation, limited photon harvesting, and high recombination losses. The development of the bulk heterojunction (BHJ) has significantly overcome these issues, resulting in dramatic improvements in organic photovoltaic performance, now exceeding 18% power conversion efficiencies. Here, the design and engineering strategies used to develop the optimal bulk heterojunction for solar‐cell, photodetector, and photocatalytic applications are discussed. Additionally, the thermodynamic driving forces in the creation and stability of the bulk heterojunction are presented, along with underlying photophysics in these blends. Finally, new opportunities to apply the knowledge accrued from BHJ solar cells to generate free charges for use in promising new applications are discussed. Abstract : The development of the bulk heterojunction, in terms of materials design, device engineering, and the underpinning physical understanding, has led to significant improvements in organic photovoltaics. Looking forward, the bulk heterojunction concept is likely to allow even greater solar cell efficiencies and interestingly, can be applied to other organic electronic applications, such as organic photodetectors and photocatalysts.